MANAGEMENT OF TYPE 2 DIABETES MELLITUS BY DIABETIC CLIENTS IN NYANDARUA SOUTH SUB - COUNTY, KENYA - Muoki, Francis M.; Kabiru, Prof. Ephantus W.; Wanyoro, Dr. Anthony K. (Global Journal of Health Sciences, 2017)
Purpose: Type 2 diabetes mellitus, (T2DM) is the most common form of diabetes, characterized by disorders of insulin resistance, insulin secretion, obesity, lipid abnormalities, hypertension, and cardiovascular diseases. The marked increase of type 2 diabetes mellitus (T2DM) necessitates active development and implementation of efficient prevention programs as the condition is a major public health concern in the world. This study sought to determine management of T2DM by diabetic clients in Nyandarua South sub-County, Kenya. Methods: A descriptive cross-sectional facility based design was used. The study population comprised 294 T2DM clients. Relationship between levels of knowledge on the recommended management interventions, socio-demographic factors and management practices were examined using chi-square and bivariate analyses. A Pâ‰¤ 0.05 was considered significant. Results: Majority of participants (83.3%) had never been screened for DM except at the point of diagnosis. A small proportion of the participants (28%) had good knowledge on T2DM management interventions. Practices applied by the clients in managing T2DM included diet, exercise, taking diabetic medications and monthly weight monitoring. Conclusions made from the study are that there was low level of knowledge on T2DM management interventions, practices for management of T2DM that participants applied included diabetic diet, exercise, drug therapy and weight monitoring though fairly undertaken. Level of education and income significantly influenced clients' management of T2DM. Recommendations: The national and Nyandarua County government's Department of Health to improve on creation of awareness on T2DM management interventions and diversify the media so as to reach most people. This should be standardized across the health facilities in order to improve the level of knowledge on management interventions for T2DM among diabetic clients. Keywords: Management, type 2 diabetes mellitus, diabetic clients